Mechanistic Insight into Antimicrobial and Antioxidant Potential of Jasminum Species: A Herbal Approach for Disease Management - Balkrishna, Acharya; Rohela, Akansha; Kumar, Abhishek; Kumar, Ashwani; Arya, Vedpriya; Thakur, Pallavi; Oleksak, Patrik; Krejcar, Ondrej; Verma, Rachna; Kumar, Dinesh; Kuca, Kamil (Plants (Basel, Switzerland), 2021)
Drug resistance among microbial pathogens and oxidative stress caused by reactive oxygen species are two of the most challenging global issues. Firstly, drug-resistant pathogens cause several fatalities every year. Secondly aging and a variety of diseases, such as cardiovascular disease and cancer, are associated with free radical generated oxidative stress. The treatments currently available are limited, ineffective, or less efficient, so there is an immediate need to tackle these issues by looking for new therapies to resolve resistance and neutralize the harmful effects of free radicals. In the 21st century, the best way to save humans from them could be by using plants as well as their bioactive constituents. In this specific context, Jasminum is a major plant genus that is used in the Ayurvedic system of medicine to treat a variety of ailments. The information in this review was gathered from a variety of sources, including books, websites, and databases such as Science Direct, PubMed, and Google Scholar. In this review, a total of 14 species of Jasminum have been found to be efficient and effective against a wide variety of microbial pathogens. In addition, 14 species were found to be active free radical scavengers. The review is also focused on the disorders related to oxidative stress, and it was concluded that Jasminum grandiflorum and J. sambac normalized various parameters that were elevated by free radical generation. Alkaloids, flavonoids (rutoside), terpenes, phenols, and iridoid glucosides are among the main phytoconstituents found in various Jasminum species. Furthermore, this review also provides insight into the mechanistic basis of drug resistance, the generation of free radicals, and the role of Jasminum plants in combating resistance and neutralizing free radicals.
Keywords: Jasminum species; reactive oxygen species; antimicrobial; antioxidants; mechanistic insight